Seed reserve composition and mobilization during germination and early seedling establishment of Cereus jamacaru D.C. ssp. jamacaru (Cactaceae) - Nara L.M. Alencar; Renato Innecco; Enéas Gomes-Filho; Maria Izabel Gallão; Juan C. Alvarez-Pizarro; José T. Prisco; Alexandre B. De Oliveira (Anais da Academia Brasileira de Ciências, 2012)
Cereus jamacaru, a Cactaceae found throughout northeast Brazil, is widely used as cattle food and as an ornamental and medicinal plant. However, there has been little information about the physiological and biochemical aspects involved in its germination. The aim of this study was to investigate its reserve mobilization during germination and early seedling growth. For this, C. jamacaru seeds were germinated in a growth chamber and collected at 0, 2, 4, 5, 6, 8 and 12 days after imbibition for morphological and biochemical analyses. Dry seeds had wrinkled seed coats and large, curved embryos. Lipids were the most abundant reserve, comprising approximately 55% and 65% of the dry mass for cotyledons and the hypocotylradicle axis, respectively. Soluble sugars and starch were the minor reserves, corresponding to approximately 2.2% of the cotyledons' dry mass, although their levels showed significant changes during germination. Soluble proteins corresponded to 40% of the cotyledons' dry mass, which was reduced by 81% at the final period of germination compared to dry seeds. C. jamacaru seed can be classified as an oil seed due to its high lipid content. Moreover, lipids were the main reserve mobilized during germination because their levels were strongly reduced after seed germination, while proteins were the second most utilized reserve in this process. Cereus jamacaru, uma cactácea encontrada comumente no nordeste brasileiro, é amplamente usada como planta forrageira e como ornamental e medicinal. No entanto, existem poucas informações sobre os aspectos fisiológicos e bioquímicos relacionados à sua germinação. O objetivo desse estudo foi avaliar a mobilização de reservas durante a germinação e o crescimento inicial de plântulas de C. jamacaru. Para isso, as sementes foram germinadas em câmaras de germinação e coletadas aos 0, 2, 4, 5, 6, 8 e 12 dias após a germinação para as análises fisiológicas e bioquímicas. As sementes quiescentes apresentaram tegumento espesso e rugoso e embriões curvados. Os lipídios foram as reservas mais abundantes, correspondendo aproximadamente a 55% e 65% da massa seca dos cotilédones e eixo hipocótilo-radícula, respectivamente. Os açúcares solúveis e o amido foram as reservas menos abundantes, correspondendo aproximadamente a 2,2% da massa seca dos cotilédones, embora suas reservas tenham apresentado mudanças significativas durante a germinação. As proteínas solúveis corresponderam a 40% da massa seca dos cotilédones, que foi reduzida a 81% no período final de germinação comparado a sementes quiescentes. As sementes de C. jamacaru podem ser consideradas oleaginosas devido ao seu alto conteúdo de lipídios. Além disso, os lipídios foram as principais reservas mobilizadas durante a germinação porque seus níveis foram fortemente reduzidos durante esse período, enquanto que as proteínas foram a segunda reserva mais utilizada nesse processo.